Propofol and sevoflurane induce distinct burst suppression patterns in rats - Kenny, Jonathan D.; Westover, M. Brandon; Ching, ShiNung; Brown, Emery N.; Solt, Ken (Frontiers in Systems Neuroscience, 2014)
Burst suppression is a pattern of brain electrical activity characterized by alternating periods of high-amplitude bursts and electrical silence. Burst suppression can arise from several different pathological conditions, as well as from general anesthesia. Here we review current algorithms that are used to quantify burst suppression, its various etiologies, and possible underlying mechanisms. We then review clinical applications of anesthetic-induced burst suppression. Finally, we report the results of our new study showing clear electrophysiological differences in burst suppression patterns induced by two common general anesthetics, sevoflurane and propofol. Our data suggest that the circuit mechanisms that generate burst suppression activity may differ between different general anesthetics.